The effect of interactive learning on nutritional knowledge among teachers, parents and students at primary schools in Central Java - Rachmawati Emma; Umniyatun Yuyun; Iqbal Nurmansyah Mochamad; Hidayati; Kharisma Saraswati Lia; Sahidin Didin; Sulistio Gohardi Virgo; Wulandari Eka (BIO Web of Conferences)
Background: Failure of linear growth or stunting is one of childhood's most common nutritional deficiencies. Parenting patterns and food provision greatly influence children's ability to consume balanced nutrition. Interactive learning transforms the educational process into a dynamic, engaging, and effective experience, providing students with applicable and long-lasting skills and knowledge. Objectives: This study identified the impact of interactive learning on nutritional knowledge among students, parents, and teachers in primary schools in Central Java. Methods: The research used a pre-post study design, involving an interactive learning process, where balanced nutrition material and relevant games were delivered to the respondents. The duration of the intervention was five hours. The research involved 252 participants from 51 primary schools. The instrument measures several important components of the government’s balanced nutrition guideline. It assesses the knowledge of children, parents, and teachers regarding the components of a plate, protein sources, children's nutritional needs, children's ideal body weight, the significance of breakfast, the role of vitamins and vegetables, the benefits of tempeh or tofu, and proper handwashing techniques. Measurements were taken before and after the intervention. Results: The pre-post test showed that there was a significant difference in nutritional knowledge in the teacher and parent groups but not in the student group (p-value: 0.751). Conclusions: Continuous efforts are needed to educate students regarding nutrition. Apart from interactive games, the lecture method can also be used to emphasize several important points during learning.